Aerosol first indirect effect over narrow longitude regions of North Pacific and same-latitude lands. (15th May 2022) - Yang, Jie; Zhao, Chuanfeng; Sun, Yue; Chi, Yulei; Yang, Yikun
Abstract: Aerosol first indirect effect (FIE), which causes variations of cloud droplet effective radius (re ) and then cloud radiative effect (CRE), is one of the critical factors leading to uncertainties in climate model simulations. Different from most previous studies over continental regions, using 10-year observation data from CERES, this study investigates the statistical relationships between aerosol optical depth (AOD) and non-precipitating single-layer liquid phase cloud re and surface shortwave CRE (CRESW ) over narrow longitude regions of North Pacific and its eastern and western lands at equal latitudes, along with the estimation of aerosol FIE. Both surface CRESW and cloud re are highly affected by aerosols. When AOD is less than 0.3–0.4 and liquid water path (LWP) is greater than 30 g/m 2, positive AOD-CRESW and negative AOD-cloud re relationships are found over both ocean and land. With the increase of AOD, the sensitivity of CRESW and cloud re to aerosol is weakened, but both have greater fluctuations. The latitude dependence of the CRESW and cloud re variations with AOD are weak. The increases in liquid water path (LWP) when LWP is in a certain range (30–120 g/m 2 over ocean and 30–90 g/m 2 over land) can highly increase CRESW and promote the growth of cloud droplets. We also find that FIE values are positive under clean condition, while negative under polluted condition. Associated with the much less aerosol amount and more sufficient water supply, the FIE values over the ocean are distinctly larger than that over the land. Highlights: FIE is distinctly larger over ocean than over land due to cleaner and moister air. The sensitivity of surface CRFSW and cloud re to AOD are high when AOD is low. The sensitivity of surface CRFSW and cloud re to AOD are low when AOD is large. Increase in LWP promotes the growth of cloud droplet sizes clearly for low LWP cases. Increase in LWP promotes the CRFsw significantly when LWP is not too high.